Analisis Kepribadian Tokoh Utama Dalam Novel Pukul Setengah Lima Karya Rintik Sedu Dengan Pendekatan Humanistis Abraham Maslow - Surya Rafi Ilham Ramadhan; Meliya Nurfiana; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research was made based on the principal of the problem that occurred in the object of the research material, which was a novel entitled Pukul setengah lima by Rintik Sedu. The aim of this research is to reveal the personality of the main character in the novel and analyze the reasons why this personality emerged. The method of this research uses qualitative literature study methods, by reading, taking notes, interpreting and the Hermeneutic method, namely interpreting sentences that are difficult to understand into something that is easy to understand or interpreting foreign languages into our language. From this research, we obtained data from Abraham Maslow’s humanistic approach, namely physiological needs, security needs, love and existence needs, self-esteem needs, and self-actualization needs. From this research it can be concluded that the main character does not fully meet these needs, the reason why this personality appears in the main character is because the main character has not reached the peak of self-actualization, he does not fulfill the needs for security and love so that the main character experiences basic anxiety and causes him not to able to reach the peak of self-actualization because lower level needs have not been fully met.